Physical activity and content in a variety of physically active learning: an observational case study of real-world practices - Johansen, Jan-Michael; Mandelid, Mathias Brekke; Reinboth, Michael; Resaland, Geir Kåre; Bratland-Sanda, Solfrid (Frontiers in Sports and Active Living, 2025)
BackgroundResearch on physically active learning (PAL) has mainly been investigated experimentally, where interventions have been introduced to study effects on, for example, physical activity (PA) levels. This might undermine real-world contexts and realistic PA levels when teachers have sustained PAL in their regular teaching practice for several years. The purpose of this study was to observe and describe the organization and content of a variety of teaching where PAL was enacted by experienced teachers and to describe the corresponding PA levels and PA intensity in real-world practices.MethodsFifty-eight pupils and four teachers from one primary school and one secondary school were enrolled across the first, sixth, and eighth grades. The pupils’ physical activity (PA) levels were assessed during 37 enacted physically active learning (PAL) segments within longer teaching lessons using waist-worn triaxial accelerometers. Evenson cut-off points were employed to define PA intensities. All enacted PAL were passively observed by the same observer regarding primary bodily movement, duration, subject, location, collaborative or individual work, and task orientation.ResultsOn average, PAL consisted of 57.8% ± 15.7% sedentary time, 22.9% ± 7.5% light intensity PA, and 19.3% ± 10.8% moderate-to-vigorous intensity PA, displaying a large variety in different PAL segments. More intensive and higher volumes of PA were evident when PAL was facilitated outdoors, in gyms, or in large stairways, while lower PA volumes and intensity were assessed when PAL was enacted inside the classroom. The primary movement in PAL was mainly running and/or walking (78.3%), while the PAL activity was mainly organized as group work (83.7%) in non-competitive tasks (97.3%).ConclusionsThis study provides novel insights by being the first to investigate the organization and content of PAL enacted by experienced teachers in their teaching and the corresponding PA levels in their real-world practices. The results displayed a large diversity in PA levels and intensities and may serve as a starting point to further investigate the coherency of PA levels and PAL content in schools with sustained PAL teaching.